Auditoría Tributaria a la Lubricadora Buenaño de la ciudad de Riobamba en el período 2012, para verificar el cumplimiento de las disposiciones tributarias. - Cárdenas Barreno, Verónica Concepción (2016)
The development of this work consists of a tax audit in the lubricator Buenaño city of Riobamba in the period 2012 to verify compliance with tax provisions. The aim of it is to check that the company has adequately complied with tax obligations, for which techniques and tools will be implemented through the information provided by the human talent of the entity. The thesis includes an ordered into chapters scheme described below: The first chapter begins with a framework describing the problem through its approach and formulation, besides the objectives of the research are described in order to be clear about what you want to accomplish with it, and describing the justified their tax significance. The second chapter corresponds to the Reference Framework is divided into units, the first unit in the history of the lubricator Buenaño flange lubrication service that is broken down; in the second, third and fourth unit the foundation of concepts given by different authors and laws referred to in theme to develop, and the fifth drive unit hypothetical states is shown The third chapter shows the methodological framework, the method developed here, the techniques, the research design and the people involved as well as the phases of the Tax Audit Planning component is get the accounting and tax knowledge lubricator Buenaño company, after the execution of this work and will develop the audit and finally the communication of results through a report in general the observations found. In the fourth chapter the conclusions and recommendations of the research work by determining the findings. In the fifth chapter the proposal that may lead to the improvement of the company. And finally the reference material attached to support the development of Audit.